Digital Content in Public Communication Efforts to Disseminate Probolinggo City Government Policies - Husni Mubaroq (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The development of information technology, especially the communication sector, creates a disruptive transition that the Government can utilize in conducting public communications. Public communication, especially in the delivery of public policies by the Government, can take advantage of the modernization of online mass media. The Probolinggo City Government also applies this in the socialization of policies in Proolinggo City. The Probolinggo City Government has social media accounts to disseminate information and policies in Probolinggo City with digital content. This research uses a conceptual review technique and a qualitative approach. The aim is to find out the application of social media such as Meta, Instagram, and Youtube owned by the Probolinggo City Government in conveying policy socialization in digital content formats. The types of digital content used are written content, image content, video content, and live streaming. We can find out the effectiveness of uploading digital content in public communication theory related to policy socialization by the Probolinggo City Government.